A eficácia das redes de cooperação jurídica direta no combate á corrupção transnacional e sua concretização pelo sistema processual brasileiro : notas sobre a Operação Lava Jato - Gubert, Paula Soares Campeão (2019)
The studies were developed in the area of Justice, Process and Constitution concentration, in the research line of Process, Constitutionality and Protection of Existential and Patrimonial Rights of the Masters in Procedural Law of the Federal University of Espírito Santo, from the contributions of the Research Groups entitled "International Law and the Maze of Codification" and "Limits and Extension of the Brazilian International Jurisdiction". Based on the premise of the corruption problem, understood as a phenomenon of public service marketing in order to obtain undue advantages, it is sought to combat the expansion of its practices in the globalized community, under the procedural point of view of international legal cooperation. By means of the inductive method of investigation, the factual clipping extracted from Criminal Action No. 5036528-23.2015.4.04.7000, in process before the 13th Court of the Federal Judicial Branch of the State of Paraná, is adopted as a particular reference, with the purpose of verifying the application of transnational networks to support the exchange of data, information and evidence, in casu. From the analysis of the concrete case, it is proposed the construction of a general knowledge about the effectiveness of the application of instruments of criminal cooperation to deal with corruption in a transnational dimension and its implementation by the Brazilian procedural system, with special focus on direct cooperation networks. Based on the line of thinking of Transnational Legal Pluralism, the concept of Global Law based on the formation of discourses and communication networks is adopted, while the reflection of arrangements in which legal multiplaces are associated and normative bundles emitted from diversified bodies communicating, integrating a spectrum of transnationality. The study is based on the collective action of transnational networks and cooperative arrangements between national regulatory authorities. Furthermore, the bases are laid specifically on the necessary respect for the fundamental rights of the human person and their assumption as the democratic limit and paradigm of the work of cooperation networks to combat criminal practices in today's global community. Finally, notes will be made on whether or not to confirm the research hypothesis, in order to determine if such networks are effective in the fight against corruption and if they are implemented in the Brazilian procedural system, drawing the respective notes on the application of cooperation networks on “Lava Jato” operation.